Detection of bacterial species from clinical mastitis in dairy cows at Nilphamari district and their antibiogram studies - Mia, Md Titon; Hossain, Md Khaled; Rumi, Nazmi Ara; Rahman, Md Shajedur; Mahmud, Md Shahin; Das, Monoranjan (Asian Journal of Medical and Biological Research, 2017)
The present study was conducted on the rural dairy cows to detect the bacterial species from clinical mastitis in dairy cows with their antibiogram studies during the period from January 2015 to June 2015. For this purpose two upazilla were selected under the Nilphamari district. On the basis of morphology, staining, cultural and biochemical characteristics, the isolated organisms were classified as, Staphylococcus spp., Streptococcus spp., E. coli, and Bacillus spp. .For this study, a total of 48 samples were collected from affected mastitis cows. Out of 48 milk samples, 17 were positive for Staphylococcus spp. (35.42%), 9 were positive for Streptococcus spp. (18.75%), 7 were positive for E. coli (14.58%), 5 were positive for Bacillus spp.(10.41%),5 were positive for mixed organisms (10.41%) and 5 were unidentified organisms (10.41%). Antibiogram studies revealed that all of the isolates of Staphylococcus spp. were sensitive to gentamicin and were resistant to streptomycin. Gentamicin was sensitive to all of the isolates of Streptococcus spp. and was resistant to streptomycin. The isolates of Bacillus spp. were sensitive to ciprofloxacin and Bacillus spp. was resistant to streptomycin. All of the isolates of E. coli were sensitive to ciprofloxacin the isolates were resistant to ampicillin and amoxicillin. Over all sensitivity revealed that ciprofloxacin, gentamicin and enrofloxacin were most efficacious. Thus, it may be recommended that ciprofloxacin, gentamicin and enrofloxacin in optimum doses would resolve most cases of clinical mastitis in dairy cows. Asian J. Med. Biol. Res. December 2016, 2(4): 656-663